Radical scavenging activity and phytochemical investigation of antioxidative compounds from stem and leaves of Leea indica species - Harun, Aiza; Daud, Shaari; Harith, Siti Suhaila; Ab Rahim, Nor Erlena Asmira; Abd Jalil, Mohd Azfar; Muhammad Rosdi, Nurul ‘Atiqah; , Fatin Azieyati; , Naila Nabihah; Mat So'ad, Siti Zaiton; Mohd Hassan, Norazian (2016)
In this paper, the potency of stem and leave extracts of Leea indica locally known as Memali from Tasik Chini, Pahang as a potent antioxidant agent had been studied. The antioxidant properties of three types of extracts was quantitatively assessed by 2,2 diphenyl-1-picrylhydrazyl ( DPPH) radical scavenging activity. The isolation of antioxidative compounds was conducted through preparative thin layer chromatography with the use of certain binary solvents. The structure determination was carried out using Gas Chromatography Mass Spectrometer (GCMS). The methanol extracts from both stem and leaves exhibited highest antioxidant activity with lowest IC50 of 24 ug/ml and 81 ug/ml respectively compared to other extracts. The stem showed stronger antioxidant activity compared to leaves part. Based on GCMS analysis, the antioxidative compounds isolated from leaves part were proposed as 6-Hyroxy-4,4, 7a-trimethyl-5,6,7,7a-tetrahydrobenzofuran-2(4H)-one (1), 3,8,8-Trimethoxy-3-piperidyl-2,2-binaphthalene-1,1,4,4-tetrone (2), Methyl stearate (3), 9,12-Octadecadienoic acid (4), Palmitic acid (5) and 9-Oxononanoic acid (6). The antioxidative compounds isolated from stem part were determined as 1- (hydroxymethyl)-1,2-ethanediyl ester (7), 9-octadecene (8) and oleic acid (9). This finding can be used as scientific baseline information for the future treatment of diseases caused by harmful free radicals.